Techno-economic analyses of solid-state anaerobic digestion and composting of yard trimmings. (15th February 2019) - Lin, Long; Shah, Ajay; Keener, Harold; Li, Yebo
Highlights: Economics of solid-state anaerobic digestion (SS-AD) and composting were evaluated. Both SS-AD and composting were found to be economically feasible. SS-AD had higher capital cost but lower non-facility operating cost than composting. Digestate drying and government financial incentives improved SS-AD economics. Both systems' profitability was most sensitive to plant size and tipping fees. Abstract: Solid-state anaerobic digestion (SS-AD) and composting are two potential alternatives to divert yard trimmings from landfills. This study aimed to evaluate the techno-economic feasibility of commercial-scale SS-AD and composting systems (20, 000 metric tons (MT)/year) that received both yard trimmings and liquid AD effluent using a modeling software, SuperPro Designer. Both the SS-AD and composting systems were shown to be economically feasible. While their revenues were comparable (48/MT), SS-AD with digestate drying showed a higher capital cost (256/MT vs. 84/MT) but a lower non-facility-dependent operating cost (11/MT vs. 21/MT) than composting. The payback time, internal rate of return (IRR), and net present value (NPV) were estimated to be ∼10 years, 8%, and 0.2 million, respectively, for SS-AD, and ∼4.9 years, 33%, and 1.8 million, respectively, for composting. Digestate drying was necessary to make SS-AD profitable via the sale of byproduct, but it was also the most energy intensive step, relying on heat recovery to reduce costs. Moreover, the economics of SS-AD were highly improved (NPV 2 million) with financial incentives (i.e. investment tax credits), indicating that incentives were critical to the economic feasibility of current SS-AD systems that utilize lignocellulosic biomass. However, renewable identification numbers (RINs) and renewable energy certificates (RECs) had minor effects. Furthermore, the economics of both systems were most sensitive to plant size, tipping fees, and byproduct/compost price. The results suggest SS-AD may be favored for centralized management while composting for de-centralized management of yard trimmings. Alternative ways to valorize digestate should be evaluated in future studies.